A modified group authentication scheme for machine type communication in LTE/LTE-a networks - Ismail, Haqi Khalid (2018)
Machine-Type Communication (MTC), as one of the essential advancements of wireless communication, has become a new business development in mobile communication. Meeting the necessities of control usage of devices and mass implement transmission is a key issue in the implementation of MTC in the Long Term Evolution/Long Term Evolution Advanced systems. Likewise, an authentication scheme is the most important piece of the system as MTC is one of the procedures that suffers under group authorization requests. The emphasis of this research is on MTC of group authentication scheme in an LTE/LTEA network that is based on a pairing-based cryptography in order to obtain a highly efficient scheme that lessens signalling congestion. In this research, an authentication scheme has been modified to enhance the performance of group authentication in an LTE/LTE-A network. High signalling congestion occurs during the verification phase since every MTC device needs to go through a full authentication process. The computation of the relevance cryptographic operations such as pairing, hashing, multiplication and XOR operations consumes time especially when a large group of MTC devices requests access to the LTE/LTE-A network simultaneously. Then, the Home Subscriber Server (HSS) verifies every request message, generates group pairing and even calculates the system keys (both private and public). Thus, an accumulation of a big number of MTC devices in a simultaneous authentication process is the main factor that causes signalling congestion as the computation requires time to authenticate the LTE/LTE-A network. Therefore, this research proposes a modified group authentication scheme for MTC in an LTE/LTE-A network in order to reduce signalling and computational overheads. The proposed method adopts two efficient algorithms, namely, the Encapsulated Double and Add algorithms which depend on the Tate Pairing form by the bilinear pairing cryptography. In the improved group authentication scheme, which has been modified, the dominance of the signalling/computational overhead time is acknowledged. The derived results indicate that the proposed approach has successfully lessened congestion problems up to 40 % in terms of computation and up to 30 % in terms of signalling overhead. In addition, the MTC devices can verify and complete a simple exchange AKA with the network. The two performance metrics used in the study are signalling overhead and computation overhead